2021
DOI: 10.1016/j.hrthm.2020.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of atrial fibrillation during the postradiofrequency ablation blanking period

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
(20 reference statements)
4
20
0
Order By: Relevance
“…Though the definition of early versus late recurrence was different in this study—within 1 month and >1 to 6 months, respectively—there were still significantly more late recurrences among the ablation patients who had early recurrences versus those who did not (52% vs. 16%, HR 4.53, p = .0006) 17 . It is also interesting to point out that in our study, 87.7% of patients without early recurrence were free from 12‐month recurrence, which is consistent with a recent meta‐analysis reporting 89% of PAF patients without early recurrence were free of longer term recurrence (≥12 months) 20 …”
Section: Discussionsupporting
confidence: 89%
“…Though the definition of early versus late recurrence was different in this study—within 1 month and >1 to 6 months, respectively—there were still significantly more late recurrences among the ablation patients who had early recurrences versus those who did not (52% vs. 16%, HR 4.53, p = .0006) 17 . It is also interesting to point out that in our study, 87.7% of patients without early recurrence were free from 12‐month recurrence, which is consistent with a recent meta‐analysis reporting 89% of PAF patients without early recurrence were free of longer term recurrence (≥12 months) 20 …”
Section: Discussionsupporting
confidence: 89%
“…In the present study we found that age was the only significant predictor for procedural complications and that CAAP-AF and CHA 2 DS 2 -VASc were the only risk scores with significant, albeit poor, predictive value.. CAAP-AF was also the risk score with the highest AUC for prediction of recurrent AF, excluding BASE-AF 2 and MB-LATER, which both incorporate early AF recurrence as a risk factor. Previous research established that recurrent AF during the blanking period is a strong predictor of recurrent AF after the blanking period (26). Scores including early recurrence cannot be used for patient selection or counseling before the ablation procedure, although these scores could theoretically be useful to determine optimal follow-up strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of ERAT in patients with persistent AF is not well characterized, since prognostic value and characteristics of early recurrences are predominantly based on data from patients with paroxysmal AF [ 1 3 , 14 , 15 ]. A recent meta-analysis investigating the predictive value of ERAT after RFCA included data which originates from ~ 90% paroxysmal AF patients, while the persistent AF population remains clearly underrepresented [ 9 ]. In the paroxysmal AF cohort, there is increasing evidence that ERAT after PVI predicts LR [ 2 , 8 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is increasing evidence that ERAT following CA for paroxysmal AF is strongly associated with late recurrence (LR) beyond the blanking period [1,2,8]. In contrast, the prognostic significance of ERAT in patients with persistent and long-standing persistent AF is poorly defined, since the majority of data (~ 90%) originates from paroxysmal AF patient cohorts [9]. RFCA for persistent AF is associated with less favorable outcomes [7] and with higher ERAT rates [10][11][12] than for paroxysmal AF.…”
Section: Introductionmentioning
confidence: 99%